BUILDING A TRANSITIONAL CARE MODEL (TCM) POLICY FLIGHT SIMULATOR. (11th November 2018) - Pennock, M J; Yu, Z; Pepe, K; Hirschman, K B; Pauly, M V; Naylor, M D; Rouse, W
Abstract: To evaluate the potential of a TCM policy flight simulator to engage individual health systems in making informed decisions regarding the adoption of TCM and increase their confidence in the decision to adopt. The TCM policy flight simulator was developed using TCM data and multiple publically available datasets and guided by the qualitative study findings. The TCM simulator was well received by all decision makers. Findings from the presentation of the TCM simulator support the value of additional tailoring to fit each organization's unique circumstances. Such tailoring would further increase decision makers' confidence regarding adoption of the TCM. Key lessons learned will be presented. The use of simulation provides a systematic tool to explore the implications and suitability of adopting the TCM for a particular organization prior to actually implementing it.